EFFECT OF RED MULBERRY JUICE (MORUS RUBRA) ON THE INFLAMMATORY RESPONSE IN MALE WISTAR RATS DUE TO EXPOSURE TO CIGARETTE SMOKE - Rivan Virlando Suryadinata; Merryana Adriani; Stefani Cornelia Sardjono (Media Gizi Indonesia, 2021)
The increasing number of tobacco users will directly impact to an increase in the number of passive smokers. Various harmful substances that enter the respiratory tract can cause health problems. The airway will recognize these substances as pathogen and activate immune response accordingly. Inﬂammatory response becomes one of the eﬀects of body compensation due to an increased pathogen. This eﬀect is indicated by the elevation of C-Reactive Protein as one systemic inﬂammatory response parameters in the body. This study aimed to determine the eﬃcacy of red mulberry juice to reduce levels of C-Reactive Protein in Wistar rats because exposure to cigarette smoke. This is an experimental study with a post-test control group design. Animals were divided into negative control group, positive control group, and 3 treatment groups with diﬀerent red mulberry doses. The positive control group showed the highest increase   in C-Reactive Protein levels compared with the red mulberry intake group (p<0,001). In conclusion, the administration of red mulberry juice can reduce inﬂammatory response in rats because of exposure to cigarette smoke.